Penguatan Kepercayaan dalam Membentuk Niat Meneruskan Penggunaan Mobile Banking - Didik Setyawan; Vincentia Alfina Miranda Damayanti; Sugiyarmasto Sugiyarmasto; Nang Among Budiadi (MBIA, 2023)
The security of using mobile banking in Indonesia is perceived as not providing a good guarantee, so it can reduce trust in continuing to use it. This study examines factors that can increase trust to influence customers' intention to continue using mobile banking. The role of user learning, the perceived value of the application, technological competence, and compatibility can strengthen trust in forming an intention to continue using. The sampling technique used was a purposive sampling technique, with 200 respondents using the BCA Mobile application, which was conducted online. Validity and reliability testing was carried out using the SPSS version 22 application. A structural approach with SEM (Structural Equation Modeling) analysis was employed to test Hypotheses. The test results show that trust in forming the intention to continue using is influenced by perceived learning, perceived value, and technological competence and is not affected by application compatibility. Keywords : Intention to Use Continuence, Trust, and Mobile Banking Abstrak Keamanan penggunaan mobile banking di Indonesia dipersepsikan belum memberikan jaminan baik yang dapat menurunkan kepercayaan untuk terus menggunakan. Studi ini mengkaji faktor-faktor yang dapat meningkatkan kepercayaan untuk dapat mempengaruhi nasabah untuk berniat terus menggunakan mobil banking. Peran pembelajaran pengguna, nilai persepsian dari aplikasi, kompetensi teknologi, dan kompatibilitas menjadi faktor yang dapat menguatkan kepercayaan dalam membentuk niat untuk terus menggunakan. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah 200 responden pengguna aplikasi BCA Mobile yang dilakukan secara online. Pengujian validitas dan reliabilitas menggunakan aplikasi SPSS versi 22. Pengujian hipotesis menggunakan pendekatan structural dengan analisa SEM (Structural Equation Modeling). Hasil pengujian menunjukkan kepercayaan dalam membentuk niat terus menggunakan dipengaruhi adanya pembelajaran yang dipersepsikan, nilai persepsian, kompetensi teknologi, dan bukan disebabkan kompatibilitas aplikasi. Kata kunci : Niat Meneruskan Pengunaan, Kepercayaan, dan Mobile Banking